The role of search frictions in the access to finance by firms - Camargo, Bruno Rodrigues (2018)
In this thesis I empirically investigate the role of non-price related search frictions in the access to finance by firms. The focus is on the relationship between these factors and how their variation in time can affect access to finance. The study uses a rich dataset of small, medium and large firms from 109 countries, mostly of them emerging economies, and of country related search friction indicators. Results show that banking outreach indicators and informational infrastructure are strongly associated with access to finance. The percentage of internet users and its variation are the most relevant of the informational variables, especially for small and medium enterprises. For large firms, the changes in fixed phone subscriptions and in the proportion of branches by population are the most relevant frictions. Results shed light on the already identifiable role of internet on financial inclusion of SMEs, and on the difference search frictions make in the access to finance depending on firm’s size.